Characterization and culture of stem cells pulp derived tissue - Zaida Moya de Calderón (2017)
This experimental research aimed to have and cultivate stem cells from pulp tissue of impacted third molars, from 20 volunteers of both genders aged between 18 and 22 years who meet the inclusion criteria and gave their consent to voluntary participation.The laboratory method comprises successive steps that begin with obtaining the sample imediata pulp for conservation in the standardized average Dullbecos Modified Eagle Medium® culture supplemented with fetal bovine serum and antibiotics solution. The technique used to obtain stem cells by enzymatic digestion was given by Gronthos et al; the expected density of cell culture was achieved after 9 days to proceed to trypsinization and continue their cultivation; then the cell passes every 3 days achieving a cell confluence of 95% at 15 days were done.Results in cell confluence is obtained by counting cells suspended in the culture medium. Cell confluence at 3 days of culture was 20% and the cells adquire ovoid, after 6 days was 40% with further stabilization in its fibroblastoid shape, at 9 days was 85% with similar appearance to fibroblasts and 15 days was 95% while retaining their phenotype.It is concluded that the pulp tissue impacted third molars is of one of the main sources of stem cells easy access, being possible to characterization and culture.